First record of the toxic shadow goby Yongeichthys nebulosus (Gobiidae: Gobiinae) from West Bengal, eastern India - Priyankar Chakraborty; Andrew Arunava Rao (Journal of Fisheries, 2025)
Herein, the first specimen-based record of Yongeichthys nebulosus (Forsskål, 1775) (Gobiidae) is reported from West Bengal, eastern India. Three individuals were collected from mangrove-associated waters in the Indian Sundarbans, one of which was preserved as a voucher specimen at the Zoological Survey of India. This record represents a north-eastward range extension for the species, which has previously been recorded from other parts of the Indian coast, including the neighbouring state of Odisha. Morphological and meristic features of the voucher specimen are consistent with published diagnoses. The discovery highlights the importance of specimen-based documentation for accurately recording species distributions and emphasises the need for sustained biodiversity monitoring in estuarine habitats.